Alien species as a driver of recent extinctions - Bellard, Céline; Cassey, Phillip; Blackburn, Tim M. (Biology letters (2005), 2016)
We assessed the prevalence of alien species as a driver of recent extinctions in five major taxa (plants, amphibians, reptiles, birds and mammals), using data from the IUCN Red List. Our results show that alien species are the second most common threat associated with species that have gone completely extinct from these taxa since AD 1500. Aliens are the most common threat associated with extinctions in three of the five taxa analysed, and for vertebrate extinctions overall.